Distributed propulsion and ultra-high by-pass rotor study at aircraft level. (November 2015) - Isikveren, A. T.; Seitz, A.; Bijewitz, J.; Mirzoyan, A.; Isyanov, A.; Grenon, R.; Atinault, O.; Godard, J.-L.; Stückl, S.
Abstract: This technical article discusses design and integration associated with distributed propulsion as a means of providing motive power with significantly reduced emissions and external noise for future aircraft concepts. The technical work reflects activities performed within a European Commission funded Framework 7 project entitled Distributed Propulsion and Ultra-high By-Pass Rotor Study at Aircraft Level, or, DisPURSAL. In this instance, the approach of distributed propulsion includes a Distributed Multiple-Fans Concept driven by a limited number of engine cores as well as one unique solution that integrates the fuselage with a single propulsor (dubbed Propulsive-Fuselage Concept) – both targeting entry-in-service year 2035+. Compared to a state-of-the-art, year 2000 reference aircraft, designs with tighter coupling between airframe aerodynamics and motive power system performance for medium-to-long-range operations indicated potentially a 40-45% reduction in CO2 -emissions. An evolutionary, year 2035, conventional morphology gas-turbine aircraft was predicted to be –33% in CO2 -emissions.